Structurally unjust: how lay beliefs about racism relate to responses to racial inequality in the criminal legal system - Rucker, Julian Michael; Duker, Ajua; Richeson, Jennifer Anne (Frontiers in Social Psychology, 2024)
Racial inequality has been a persistent component of American society since its inception. The present research investigates how lay beliefs about the nature of racism—as primarily caused by prejudiced individuals or, rather, to structural factors (i.e., policies, institutional practices) that disadvantage members of marginalized racial groups—predict reactions to evidence of racial inequality in the criminal legal system (Studies 1–3). Specifically, the current research suggests that holding a more structural (vs. interpersonal) view of racism predicts a greater tendency to perceive racial inequality in criminal legal outcomes. Moreover, White Americans' lay beliefs regarding racism, coupled with their general degree of preference for societal hierarchy, predict support for policies that would impact disparities in the U.S. prison population. Together, this work suggests that an appreciation of structural racism plays an important role in how people perceive and respond to racial inequality.